Low Cycle Fatigue Performance of Additively Processed and Heat-Treated Ti-6Al-7Nb Alloy for Biomedical Applications - Hein, Maxwell; Kokalj, David; Lopes Dias, Nelson Filipe; Stangier, Dominic; Oltmanns, Hilke; Pramanik, Sudipta; Kietzmann, Manfred; Hoyer, Kay-Peter; Meißner, Jessica; Tillmann, Wolfgang; Schaper, Mirko (Metals)
In biomedical engineering, laser powder bed fusion is an advanced manufacturing technology, which enables, for example, the production of patient-customized implants with complex geometries. Ti-6Al-7Nb shows promising improvements, especially regarding biocompatibility, compared with other titanium alloys. The biocompatible features are investigated employing cytocompatibility and antibacterial examinations on Al2O3-blasted and untreated surfaces. The mechanical properties of additively manufactured Ti-6Al-7Nb are evaluated in as-built and heat-treated conditions. Recrystallization annealing (925 °C for 4 h), β annealing (1050 °C for 2 h), as well as stress relieving (600 °C for 4 h) are applied. For microstructural investigation, scanning and transmission electron microscopy are performed. The different microstructures and the mechanical properties are compared. Mechanical behavior is determined based on quasi-static tensile tests and strain-controlled low cycle fatigue tests with total strain amplitudes εA of 0.35%, 0.5%, and 0.8%. The as-built and stress-relieved conditions meet the mechanical demands for the tensile properties of the international standard ISO 5832-11. Based on the Coffin–Manson–Basquin relation, fatigue strength and ductility coefficients, as well as exponents, are determined to examine fatigue life for the different conditions. The stress-relieved condition exhibits, overall, the best properties regarding monotonic tensile and cyclic fatigue behavior.
Keywords: General Materials Science; Metals and Alloys; laser powder bed fusion; Ti-6Al-7Nb; titanium alloy; biomedical engineering; low cycle fatigue; microstructure; nanostructure

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Science and Engineering: A)
In order to reduce CO2 emissions in the transport sector, the approach of load-adapted components is increasingly being pursued. For the design of such components, it is crucial to determine their resulting microstructure and mechanical properties. For this purpose, continuous cooling transformation diagrams and deformation continuous cooling transformation diagrams are utilized, however, their curves are strongly influenced by the chemical composition, the initial state and especially the process parameters. In this study, the influence of the process parameters on the transformation kinetics is systematically investigated using an innovative characterization method. The experimental setup allowed a near-process analysis of the transformation kinetics, resulting microstructure and mechanical properties for a specific process route with a reduced number of specimens. A systematic investigation of the effects of different process parameters on the microstructural and mechanical properties made it possible to reveal interactions and independencies between the process parameters in order to design a partial heating or differential cooling process. Furthermore, the implementation of two different cooling conditions, representative of differential cooling in the die relief method with tool-contact and non-contact areas, showed that the soaking duration has a significant influence on the microstructure in the non-contact tool area.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization and analysis of plastic instability in an ultrafine‐grained medium Mn TRIP steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlon; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Additively Manufactured Nested and Non-Nested Cellular Solids for Effective Stress Distribution and Thermal Insulation Applications: An Experimental and Finite Element Analysis Study - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
In this study, the design, additive manufacturing and experimental as well as simulation investigation of mechanical and thermal properties of cellular solids are addressed. For this, two cellular solids having nested and non-nested structures are designed and additively manufactured via laser powder bed fusion. The primary objective is to design cellular solids which absorb a significant amount of energy upon impact loading without transmitting a high amount of stress into the cellular solids. Therefore, compression testing of the two cellular solids is performed. The nested and non-nested cellular solids show similar energy absorption properties; however, the nested cellular solid transmits a lower amount of stress in the cellular structure compared to the non-nested cellular solid. The experimentally measured strain (by DIC) in the interior region of the nested cellular solid is lower despite a higher value of externally imposed compressive strain. The second objective of this study is to determine the thermal insulation properties of cellular solids. For measuring the thermal insulation properties, the samples are placed on a hot plate; and the surface temperature distribution is measured by an infrared camera. The thermal insulating performance of both cellular types is sufficient for temperatures exceeding 100 °C. However, the thermal insulating performance of a non-nested cellular solid is slightly better than that of the nested cellular solid. Additional thermal simulations predict a relatively higher temperature distribution on the cellular solid surfaces compared to experimental results. The simulated residual stress shows a similar distribution for both types, but the magnitude of residual stress is different for the cellular solids upon cooling from different temperatures of the hot plate.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

LPBF Manufactured Functionally Graded Lattice Structures Obtained by Graded Density and Hybrid Poisson’s Ratio - Abdelaal, Osama; Hengsbach, Florian; Schaper, Mirko; Hoyer, Kay-Peter (Materials)
The additive manufacturing (AM) of innovative lattice structures with unique mechanical properties has received widespread attention due to the capability of AM processes to fabricate freeform and intricate structures. The most common way to characterize the additively manufactured lattice structures is via the uniaxial compression test. However, although there are many applications for which lattice structures are designed for bending (e.g., sandwich panels cores and some medical implants), limited attention has been paid toward investigating the flexural behavior of metallic AM lattice structures with tunable internal architectures. The purpose of this study was to experimentally investigate the flexural behavior of AM Ti-6Al-4V lattice structures with graded density and hybrid Poisson’s ratio (PR). Four configurations of lattice structure beams with positive, negative, hybrid PR, and a novel hybrid PR with graded density were manufactured via the laser powder bed fusion (LPBF) AM process and tested under four-point bending. The manufacturability, microstructure, micro-hardness, and flexural properties of the lattices were evaluated. During the bending tests, different failure mechanisms were observed, which were highly dependent on the type of lattice geometry. The best response in terms of absorbed energy was obtained for the functionally graded hybrid PR (FGHPR) structure. Both the FGHPR and hybrid PR (HPR) structured showed a 78.7% and 62.9% increase in the absorbed energy, respectively, compared to the positive PR (PPR) structure. This highlights the great potential for FGHPR lattices to be used in protective devices, load-bearing medical implants, and energy-absorbing applications.
Keywords: General Materials Science

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Heat Treatments of Metastable β Titanium Alloy Ti-24Nb-4Zr-8Sn Processed by Laser Powder Bed Fusion - Hein, Maxwell; Lopes Dias, Nelson Filipe; Pramanik, Sudipta; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (Materials)
Titanium alloys, especially β alloys, are favorable as implant materials due to their promising combination of low Young’s modulus, high strength, corrosion resistance, and biocompatibility. In particular, the low Young’s moduli reduce the risk of stress shielding and implant loosening. The processing of Ti-24Nb-4Zr-8Sn through laser powder bed fusion is presented. The specimens were heat-treated, and the microstructure was investigated using X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The mechanical properties were determined by hardness and tensile tests. The microstructures reveal a mainly β microstructure with α″ formation for high cooling rates and α precipitates after moderate cooling rates or aging. The as-built and α″ phase containing conditions exhibit a hardness around 225 HV5, yield strengths (YS) from 340 to 490 MPa, ultimate tensile strengths (UTS) around 706 MPa, fracture elongations around 20%, and Young’s moduli about 50 GPa. The α precipitates containing conditions reveal a hardness around 297 HV5, YS around 812 MPa, UTS from 871 to 931 MPa, fracture elongations around 12%, and Young’s moduli about 75 GPa. Ti-24Nb-4Zr-8Sn exhibits, depending on the heat treatment, promising properties regarding the material behavior and the opportunity to tailor the mechanical performance as a low modulus, high strength implant material.
Keywords: General Materials Science

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Orive, Alejandro Gonzalez; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Characterization and Analysis of Plastic Instability in an Ultrafine‐Grained Medium Mn TRIP Steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlong; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Gonzalez Orive, Alejandro; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Modification of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Additively Manufactured Nested and Non-Nested Cellular Solids for Effective Stress Distribution and Thermal Insulation Applications: An Experimental and Finite Element Analysis Study - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
In this study, the design, additive manufacturing and experimental as well as simulation investigation of mechanical and thermal properties of cellular solids are addressed. For this, two cellular solids having nested and non-nested structures are designed and additively manufactured via laser powder bed fusion. The primary objective is to design cellular solids which absorb a significant amount of energy upon impact loading without transmitting a high amount of stress into the cellular solids. Therefore, compression testing of the two cellular solids is performed. The nested and non-nested cellular solids show similar energy absorption properties; however, the nested cellular solid transmits a lower amount of stress in the cellular structure compared to the non-nested cellular solid. The experimentally measured strain (by DIC) in the interior region of the nested cellular solid is lower despite a higher value of externally imposed compressive strain. The second objective of this study is to determine the thermal insulation properties of cellular solids. For measuring the thermal insulation properties, the samples are placed on a hot plate; and the surface temperature distribution is measured by an infrared camera. The thermal insulating performance of both cellular types is sufficient for temperatures exceeding 100 °C. However, the thermal insulating performance of a non-nested cellular solid is slightly better than that of the nested cellular solid. Additional thermal simulations predict a relatively higher temperature distribution on the cellular solid surfaces compared to experimental results. The simulated residual stress shows a similar distribution for both types, but the magnitude of residual stress is different for the cellular solids upon cooling from different temperatures of the hot plate.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

LPBF Manufactured Functionally Graded Lattice Structures Obtained by Graded Density and Hybrid Poisson’s Ratio - Abdelaal, Osama; Hengsbach, Florian; Schaper, Mirko; Hoyer, Kay-Peter (Materials)
The additive manufacturing (AM) of innovative lattice structures with unique mechanical properties has received widespread attention due to the capability of AM processes to fabricate freeform and intricate structures. The most common way to characterize the additively manufactured lattice structures is via the uniaxial compression test. However, although there are many applications for which lattice structures are designed for bending (e.g., sandwich panels cores and some medical implants), limited attention has been paid toward investigating the flexural behavior of metallic AM lattice structures with tunable internal architectures. The purpose of this study was to experimentally investigate the flexural behavior of AM Ti-6Al-4V lattice structures with graded density and hybrid Poisson’s ratio (PR). Four configurations of lattice structure beams with positive, negative, hybrid PR, and a novel hybrid PR with graded density were manufactured via the laser powder bed fusion (LPBF) AM process and tested under four-point bending. The manufacturability, microstructure, micro-hardness, and flexural properties of the lattices were evaluated. During the bending tests, different failure mechanisms were observed, which were highly dependent on the type of lattice geometry. The best response in terms of absorbed energy was obtained for the functionally graded hybrid PR (FGHPR) structure. Both the FGHPR and hybrid PR (HPR) structured showed a 78.7% and 62.9% increase in the absorbed energy, respectively, compared to the positive PR (PPR) structure. This highlights the great potential for FGHPR lattices to be used in protective devices, load-bearing medical implants, and energy-absorbing applications.
Keywords: General Materials Science

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Increasing the accuracy of clinching process simulations by modeling the friction as a function of local joining process parameters - Rossel, Moritz Sebastian; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In this study, an innovative friction model is used to improve the quality of clinching process simulations. Consequently, the future over dimensioning can be reduced. Furthermore, the improved prediction quality of the joining process simulation leads to an improvement in the simulation of load-bearing capacity as well. In this way, the entire sampling process can be performed virtually without any experimental investigations. This will contribute to the advancement of lightweight construction in the automotive industry. In this work, the frictional behavior is studied in dependence on the local joining process parameters. As a reference for the numerical investigations, clinch joints by means of a die with fixed geometry are joined. Additionally, a hardness mapping is performed on the microsection of the clinch joints. It shows the local strain hardening, which correlates with the forming degree in the simulation. Based on the occurring contacts and the local joining process parameters in the joining process simulation, the test matrix for the experimental friction tests is defined. The friction tests are carried out on a compression-torsion-tribometer. This type of tribometer is able to apply high interface pressures above the initial yield stress due to the specimen encapsulation. Besides, the pure joining part contact, the contact between the joining part and joining tool can be tested as well. The experimental test setup offers the possibility to evaluate the influences of temperature, relative velocity, interface pressure, and frictional stroke independently. Based on the results of the experimental friction tests, a friction model is created. The resulting friction model is integrated into the numerical joining process simulation via a subroutine. To validate the quality of the new friction modeling, the results of simulations are compared with the experiments in terms of load-stroke diagrams, joint geometry, and hardness mappings on the microsection.
Keywords: Mechanical Engineering; General Materials Science

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science